2019
DOI: 10.1186/s12885-019-6261-5
|View full text |Cite
|
Sign up to set email alerts
|

Tumor budding outperforms ypT and ypN classification in predicting outcome of rectal cancer after neoadjuvant chemoradiotherapy

Abstract: Background: Budding is a complementary prognostic factor for colorectal cancer. In this study, we aimed to clarify the role of tumor budding in rectal cancer patients after preoperative chemoradiotherapy. Methods: A total of 124 patients with rectal cancer treated with neoadjuvant chemoradiotherapy and consecutive surgery were included. Surgical specimens were evaluated for budding and routine clinicopathological features. Budding was evaluated on hematoxylin and eosin (H&E)-stained slides and by cytokeratin i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
4
20
0
Order By: Relevance
“…This assumption is also supported by the observation that the distribution of budding groups in our neoadjuvant cohort is generally in line with those described for primary resected GCs [16]. Our data almost perfectly recapitulate post-neoadjuvant studies from rectal or oesophageal carcinomas, where TB remains a stage-independent prognostic parameter that even outperformed conventional ypTNM staging [18][19][20][21]. Therefore, we believe that the assessment of TB can serve as a very strong additional histopathological parameter that should be included in the pathology reports of GCs after neoadjuvant treatment.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This assumption is also supported by the observation that the distribution of budding groups in our neoadjuvant cohort is generally in line with those described for primary resected GCs [16]. Our data almost perfectly recapitulate post-neoadjuvant studies from rectal or oesophageal carcinomas, where TB remains a stage-independent prognostic parameter that even outperformed conventional ypTNM staging [18][19][20][21]. Therefore, we believe that the assessment of TB can serve as a very strong additional histopathological parameter that should be included in the pathology reports of GCs after neoadjuvant treatment.…”
Section: Discussionsupporting
confidence: 89%
“…TB has been identified as a highly valuable histopathological parameter in a plethora of carcinoma entities throughout the body [ 8 , 12 , 13 , 14 , 15 , 38 , 39 , 40 , 41 ] and recent studies on other gastrointestinal carcinomas were able to demonstrate that, as opposed to conventional grading systems, TB remains a reliable prognosticator even after neoadjuvant therapy [ 18 , 19 , 20 , 21 ]. For GC, several previous studies have already demonstrated the high prognostic relevance of TB in therapy‐naïve tumours [ 16 , 22 , 23 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, most guidelines do not recommend evaluating TB postneoadjuvant therapy owing to insufficient data supporting its prognostic significance in this setting and concerns regarding the distinction of true TB from treatment effect 5. A growing number of studies, however, suggest that TB may retain prognostic significance in the postneoadjuvant setting 30–32. We found TB, PDC, and CS to all be significantly associated with RFS, DSS, and OS in the neoadjuvant treated group, further supporting the prognostic utility of these features in this setting.…”
Section: Discussionmentioning
confidence: 61%
“…In recent years, it was found that tumor budding has important diagnostic value in the clinicopathology and prognosis of gastrointestinal tumors ( 3 , 4 ). The incidence of tumor budding in rectal cancer cases with lymph node metastasis and lymphatic invasion is significantly higher than in those without lymph node metastasis, while local recurrence and liver metastasis are also more common in those with tumor budding ( 5 ). The incidences of tumor budding and lymph node metastasis among rectal cancer patients are closely related to TNM stage.…”
Section: Introductionmentioning
confidence: 99%